Mechanical Ventilation And Beyond: A Comprehensive Review Of Nursing Roles In Weaning Protocols And Respiratory Therapy (The Review of Diabetic Studies, 2024)
BackgroundMechanical ventilation is a cornerstone of intensive care for critically ill patients, yet prolonged use increases risks of complications like ventilator-associated pneumonia and ICU length of stay. Nurse-led weaning protocols have emerged as evidence-based strategies to shorten ventilation duration and improve outcomes, shifting from physician-driven to integrated, multiprofessional models.​MethodsThis comprehensive review synthesizes evidence from randomized controlled trials, quasi-experimental studies, observational cohorts, qualitative research, and concept analyses on nursing roles in weaning protocols and respiratory therapy. A conceptual framework maps nursing contributions across stabilization, active weaning, and post-extubation recovery.​ResultsNurse-led protocols reduced mechanical ventilation duration by 1-2 days, ICU stays, and ventilator-associated events compared to physician-led care. Key predictors like Rapid Shallow Breathing Index (RSBI